2021
DOI: 10.35691/jbm.1202.0174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drought on Trichome Density and Length in Cotton (Gossypium Hirsutum)

Abstract: Cotton is a major cash crop and backbone of the textile industry in Pakistan which is badly affected by sucking insects. Drought is an important abiotic factor in trichome development. The objective of the study was to determine the effects of drought on trichome density and length. Trichome density was measured in two ways, one through the scaling method and the other through counting the trichome density manually. The scaling method is qualitative grading while quantitative grading includes trichomecount in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Here, we found a moderately negative correlation between g S and trichome density, and this is consistent with the PCA results of Shahzad et al [ 34 ], who concluded that trichome density decreased with g S and photosynthesis rate. The results of the present study can be explained by the ability of trichomes to directly control gas fluxes and diffusion resistance in the leaves by increasing the leaf boundary layer, which can influence the transfer of CO 2 in the leaf.…”
Section: Discussionsupporting
confidence: 93%
“…Here, we found a moderately negative correlation between g S and trichome density, and this is consistent with the PCA results of Shahzad et al [ 34 ], who concluded that trichome density decreased with g S and photosynthesis rate. The results of the present study can be explained by the ability of trichomes to directly control gas fluxes and diffusion resistance in the leaves by increasing the leaf boundary layer, which can influence the transfer of CO 2 in the leaf.…”
Section: Discussionsupporting
confidence: 93%
“…By increasing the boundary layer on the leaf surface, trichomes can also reduce the plant's solar radiation absorption and decrease its temperature, thereby mitigating the risk of drought (Schreuder et al, 2001). In the current study, morphological structures of trichomes showed greater density in drought stress conditions and under the application of biochar and PGPR which are in line with findings reported previously (Liu and Liu, 2016;Shahzad et al, 2021), who found that density and length of trichomes increased under drought stress, and further improvement was attributed to the microorganisms used (PGPR).…”
Section: Discussionsupporting
confidence: 92%
“…Trichomes are a part of the plant that are above the plant epidermal tissue with various functions. Several previous studies stated the ability of trichomes to protect plants from herbivorous insects (Ebrahimi et al, 2022;Salazar-Mendoza et al, 2023), UV radiation (Rai and Agrawal, 2020;Karabourniotis et al, 2021), pathogens (Kono and Shimizu, 2020), and excessive transpiration (Shahzad et al, 2021), and influence seed protection (Li et al, 2021). This aspect is evidenced by the shape of the ends of the trichomes, which do not form a circle (taper) (Watts and Kariyat, 2022).…”
Section: Trichomes Form On Soybean Leaves and Podsmentioning
confidence: 99%